Implementing educational innovation: learning from the classroom interaction of effective Bahasa Melayu teachers in Malaysia - Konting, Mohd Majid (Universiti Putra Malaysia Press, 1997)
This paper reports a study on classroom teaching techniques five years after the implementation of the Integrated Curriculum for Secondary Schools (KBSM) in Malaysia. Systematic observation was made of the classroom practices of 12 Bahasa Melayu teachers who were identified as effective in their teaching of 12-13 year-old pupils. Contrary to the philosophy of the KBSM, the teachers were inclined to use traditional whole class teaching strategies and to dominate classroom interaction. The study concludes that there is a need to consider the existing teachers' professional knowledge and their beliefs about the notion of good practice when designing and implementing in-service teacher education programmes.